A new species of Clinocera Meigen (Diptera: Empididae) from China - Yang, Ding; Grootaert, Patrick; Horvat, Bogdan (Zootaxa, 2005)
Clinocera guangdongensis sp. n., a new aquatic dance fly of the subfamily Clinocerinae (Diptera, Empididae) is described from China. Relationships with other described species are discussed. The species of Clinocera from China are keyed. The biogeographic distribution of the genus in China is discussed.